Analysis of strategies in de bovine livestock: application of the real options games framework - Perez, Santiago Agustin; Ferro Moreno, Santiago; Milanesi, Gastón Silverio (Estudios de Administración, 2023)
The beef cattle production model is characterized by being a process of sequential stages until the finished animal is achieved. At present, the valuation of decisions under contexts typical of the activity is linear and static. In the present work, a production and commercial decision model is analyzed and evaluated, considering market risks, technological risks and flexibility values ​​of possible strategies to reach the final phase of the production process. A multinomial model is proposed using exotic real options of the rainbow type. The development of a decision tree that allows describing the operation is carried out, as well as the mathematical approach and its due valuation. Real models were used in cases of livestock in the Pampas region at values ​​of March 2022. As results, it can be extracted what decision to make considering a single scenario, and with the comparison with the strategies according to positive and negative scenarios of the activity. It can be concluded with the potential, simplicity and advantages that the development and application of a real options model allows, valuing the strategic flexibility of the decisions, applied to the livestock complex.